(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Objective The present investigation to study the diversity and uses of medicinal plants self-growing at wasteland of nearby Agra region.Methods Quadrate method was applied each site for-know the diversity richness of self-growing plants. After quadrate put at different sites, biodiversity evaluation of naturalized plants with the help of following formulas.Results Argemone maxicana have maximum biodiversity at natural 04 sites and Sida Spinosa showed minimum biodiversity. As per our result, Sida Spinosa has a minimum Biodiversity Index, so we can conserve at the botanical garden in ex-situ conservation and Argemone maxicana has maximum biodiversity, so we use this plant in treatments of human diseases in Ayurveda.